Analisis Faktor Risiko Kejadian Musculoskletal Disorders (MSDS) Pada Pekerja Officer dan Welder Menggunakan Metode Nordic Body Map di PT XYZ Kota Batam - Sari, Chinta Yolanda (LPPM Universitas Ibnu Sina, 2024)
Musculoskeletal Disorders (MSDS) is an occupational risk characterized by complaints in the muscles. MSDS occurs due to incorrect body posture while working which causes muscles to stretch too hard over a long period of time. PT. Officer and welder workers are at risk of MSDS occurring which is caused by many factors. This research is descriptive analytical with a total population of 30 officers and welders. The sampling technique uses saturated samples and primary and secondary data sources. Data collection methods are field observation, questionnaires and interviews. The research instrument was a checklist using the Nordic Body Map (NBM), a list of question items and interview guidelines. The research results show that there is an influence of work period, length of work and work attitude on the incidence of MSDS. Based on the results of the simple logistic regression test, the length of service variable was p=0.027 and OR 10.00 CI 95% (0.994-100.612). The length of work variable obtained a value of p=0.010 and OR CI 95% 13.71 (1.381-136.212) and the work attitude variable had a value of p=0.003 CI 95% 18.66 (1.879-185.399).